The The Effect of Age and Breed on The Quality of Bull Semen in The Regional Artificial Insemination Centre - Ardian Faiz Hafid; Brian Wicaksono; Kharisma Mutiara Insani; Migi Herdinta; Agung Budiyanto; Makruf Arif; Mandala Phivi Whelma Alfons; Rifia Tiara Fani (Acta VETERINARIA Indonesiana, 2021)
The success of beef cattle reproduction development in Indonesia very much depends on the quality of the semen produced by the Indonesian Institute for Artificial Insemination. Good quality bull will benefit farmers, frozen semen producers, and the country in large. This study aimed to determine effect of age and breed on the libido and quality of bull semen collected in the Regional Artificial Insemination Center (RAIC). This study used PO, Simmental, and Brahman Bull in RAIC Yogyakarta, with a total amount of 15, aged 4-7 years old. Semen was collected using an artificial vagina, semen evaluation used a spectrophotometer, and eosin-nigrosin staining method used for sperm viability and abnormalities examination. The result of this study indicated that bull breed did not affect the libido value and the semen quality of bulls (P>0,05). Volume, concentration, motility, and viability in various age groups did not show significant differences (P>0,05), but age groups had a significant effect on sperm abnormalities (P<0,05). The group of bulls aged 5-6 years showed the best quality compared to other groups, with the volume 4,58 ± 1,37 ml, concentration 1,91 ± 0,36 x109/ml, motility 3,80 ± 1,30, viability 89.83 ± 10.69%, and sperm abnormalities 2.51 ± 0.81%. It can be concluded that breed did not affect the bull libido and semen quality, while age had an effect on bull sperm abnormalities.